Kinetics of clusters formation and accumulation in crystal under cascade-generating irradiation - M. V. Kobets; P. O. Selyshchev; V. I. Slisenko (Ядерна фізика та енергетика)
Formation of point defect clusters under cascade-generating irradiation is theoretically investigated. Steady-state size distribution of cluster and its dependence on parameters is obtained. A simplified system of kinetic equations for describing of clusters formation in quasi-stationary approximation was proposed. Time dependencies of point defects concentrations and their clusters for original and simplified systems were plotted, their comparative analysis was performed.